NEOLIBERALISM AND EDUCATION: APPROACHES BETWEEN BRAZIL AND CHILE (Revista Contexto & Educação, 2022)
The present work aims to bring together Brazil and Chile in the educational field. We think that, because they are both under the influence of neoliberal ideas and have similar socioeconomic elements, is constructive to have a discussion about education in an interconnected way. Both countries have, under the influence of neoliberalism, decentralized education systems and private sector participation with large-scale evaluations whose effectiveness has been questioned. These characteristics reflected in the deepening of inequality, differentiating not only schools and universities, but also students. Evidence of this are the popular manifestations with demands in the area of ​​education that have taken place in recent years in Chile and, more recently, in Brazil, some of which have the same claims. Thus, the application of the neoliberal ideology in education has caused negative consequences in both countries, such as an increase in educational inequality and deterioration in quality. Therefore, it is imperative that we analyze the experiences already consolidated in Chile to understand the consequences that are boiling in Brazil, considering neoliberalism and its influence on education as a supranational phenomenon.
Keywords: neoliberalism and education; Latin America; educational policies